Familial dystonic choreoathetosis with myokymia; a sleep responsive disorder. Issue 12 (December 1991) - Byrne, E; White, O; Cook, M
Abstract : A family is presented with paroxysmal dystonic choreoathetosis transmitted as a dominant trait over five generations. The family is unusual in the marked responsiveness of the episodes to short periods of sleep in several members, in the very variable age of onset, and in the association with prominent myokymia in some cases. These overlap features suggest a link between paroxysmal dystonic choreoathetosis and familial paroxysmal ataxia with myokymia.